METHODS OF FORMING COLOR CODES IN HISTORICAL AREAS OF THE CITY, THE INFLUENCE OF ARCHITECTURAL STYLE ON DESIGN AND CODE (CAHIERS MAGELLANES-NS, 2024)
The need to create design-code rules for the historical areas of cities, to classify the streets and roads based on the design-code rules is one of the important tasks of today. The revolutionary changes in the historical part of the city, the destruction of traditional urban structures are caused by the streets, which are an integral part of urban development. Due to improperly organized urban infrastructure constructions, the historical region loses its national-artistic identity, socio-cultural, compositional stability is disturbed. The research examines the historical regions of the ancient cities of Uzbekistan, Bukhara and Samarkand, and considers the methods of forming color codes for historical regions based on the color and stylistic solutions of the oldest architectural monuments in them.